2009
DOI: 10.1002/jez.b.21308
|View full text |Cite
|
Sign up to set email alerts
|

Do molecular signals from the conceptus influence endometrium decidualization in rodents?

Abstract: A critical period in establishing pregnancy occurs after the onset of implantation but before placental development. Evidence strongly suggests that abnormalities occurring during this period can result in pregnancy termination or in pre-eclampsia; the latter may lead to small-for-gestational-weight offspring that are likely to be unhealthy. Clearly, events occurring in the endometrium during the implantation process are crucial for proper fetal development and for optimal offspring health. In several mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 198 publications
(257 reference statements)
0
11
0
Order By: Relevance
“…The disappearance of primary decidual zone which forms a barrier surrounding the embryo and reduced immune cell population in deciduoma further emphasize the importance of embryo-uterus dialogue (Herington and Bany, 2007b; Wang et al, 2004d). Using microarray approaches, the differentially expressed genes responsive to (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011)the living embryo versus artificial stimuli further prove the paracrine signals from the embryo regulating the decidua development (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011). Collectively, these findings highlight the necessity of embryo-derived signals for normal implantation and decidualization.…”
Section: Embryonic Preparation For Implantation Necessitates “Blasmentioning
confidence: 96%
“…The disappearance of primary decidual zone which forms a barrier surrounding the embryo and reduced immune cell population in deciduoma further emphasize the importance of embryo-uterus dialogue (Herington and Bany, 2007b; Wang et al, 2004d). Using microarray approaches, the differentially expressed genes responsive to (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011)the living embryo versus artificial stimuli further prove the paracrine signals from the embryo regulating the decidua development (Bany and Cross, 2006; Herington and Bany, 2007a; Herington and Bany, 2007b, 2009; Herington et al, 2009; Kashiwagi et al, 2007; McConaha et al, 2011). Collectively, these findings highlight the necessity of embryo-derived signals for normal implantation and decidualization.…”
Section: Embryonic Preparation For Implantation Necessitates “Blasmentioning
confidence: 96%
“…Previous work has suggested that the mammalian conceptus may secrete paracrine factors that can regulate endometrial gene expression during decidualization (reviewed in (Herington & Bany 2009)). Clear examples of this exist in several species.…”
Section: Introductionmentioning
confidence: 99%
“…AKT is mainly distributed in the luminal and glandular epithelial cells of the uterus in mice before follicular implantation. However, AKT was also detected in decidualized matrix cells (Herington and Bany, 2009). These findings indicate that activation of AKT is involved in the remodeling of endometrium and egg implantation, while miscarriage and infertility in women with thin endometrium could be associated with decreased expression of PI3K and AKT.…”
Section: Pi3kmentioning
confidence: 99%